Morphological characterization and diversity analysis of local mango (Mangifera indica L.) genotypes from far western hill of Nepal: Morphological diversity analysis of local mango - Pandey, Bhawani; Poudel, Puspa Raj; Joshi, Bal Krishna; Pathak, Rukmagat (SAARC Journal of Agriculture, 2022)
Mango is an important tropical fruit of Nepal. Nepal is rich in mango diversity and large numbers of local genotypes have been identified in different parts of the country. Such diversity of local mango genotypes are in verge of danger and needs to properly identified, evaluated and conserved. Morphological characterization is an important step in the characterization, evaluation and further utilization of genotypes. The current study aimed to characterize 33 local mango genotypes from Doti district of Far Western Region in Nepal using 14 quantitative morphological traits. The results of the study showed variation in terms tree, leaf, fruit, stone and seed character among the genotypes. The average fruit weight of genotypes was found to be 51.61g with maximum weight of 90.92g in Gude genotype. The four major principal components were formed with Eigen value >1 with cumulative diversity of 88.2%. Results of the cluster analysis grouped 33 mango genotypes into four major clusters with similarity level of 41.27% to 96.29% showing diversity among the genotypes. The variability seen among the genotypes in the present study can be a source of gene pool for systematic mango breeding program and thus these genotypes need to be properly conserved. SAARC J. Agric., 20(2): 57-67 (2022)